SME competitiveness: an internationalization strategy for Dom Pedro Hotels - Feldmann, Hannah Henrike (2013)
This paper studies the internationalization process of Dom Pedro to South Brazil. The company’s strategy is critically assessed and it is argued that a professionalization of corporate strategic planning is needed regarding further internationalization. This finding combined with a regional macro environment and hotel industry scanning helps deriving success factors for an expansion to South Brazil. Building on those factors, the market is analyzed regarding the most favorable hotel location and typology and an implementation plan is proposed. It is concluded that a business hotel in Porto Alegre represents a reasonable investment opportunity, if connected to an improved strategic planning.